Relationships among wood anatomy, hydraulic conductivity, density and shear parallel to the grain in the wood of 24-year-old Handroanthus vellosoi (Bignoniaceae) - Eduardo Luiz Longui (Rodriguésia)
Abstract We studied the relationships among wood anatomy, hydraulic conductivity, density and shear parallel to the grain in the stem of Handroanthus vellosoi trees with the goal to identify possible trade-offs between hydraulic conductivity and mechanical properties. For this study we felled 12 trees with 24-year-old and cut 10-cm-thick disks at three heights: base of the trunk, one meter in height, and two meters in height. We propose that the relationship between hydraulic conductivity and mechanical resistance found along the H. vellosoi trunk indicates greater mechanical investment in the wood at the base of the trunk compared with the other two heights (1 and 2 meters). Anatomically, this would be represented by smaller diameter vessels and fibers with thicker walls. Consequently, strength investment implies lower water conductivity at the stem base. However, more studies are needed to determine whether this lower value with respect to 1 and 2 meters represents a significant effect on water transport along the stem.